1998
DOI: 10.1038/28839
|View full text |Cite
|
Sign up to set email alerts
|

Energy and trace-gas fluxes across a soil pH boundary in the Arctic

Abstract: Studies and models of trace-gas flux in the Arctic consider temperature and moisture to be the dominant controls over land-atmosphere exchange 1,2 , with little attention having been paid to the effects of different substrates. Likewise, current Arctic vegetation maps for models of vegetation change recognize one or two tundra types 3,4 and do not portray the extensive regions with different soils within the Arctic. Here we show that rapid changes to ecosystem processes (such as photosynthesis and respiration)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
128
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(135 citation statements)
references
References 23 publications
7
128
0
Order By: Relevance
“…On the northern fringe of the foothills, soils formed in Holocene loess (Walker and Everett 1991) and soil pH changes from pH 7.7 in Site 5 to pH 5.6 in Site 6 as BS drops from 100% to 34-70%. Sites 5 and 6 represent two soils across the MNT and MAT boundary.…”
Section: Soil Ph and Base Saturationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the northern fringe of the foothills, soils formed in Holocene loess (Walker and Everett 1991) and soil pH changes from pH 7.7 in Site 5 to pH 5.6 in Site 6 as BS drops from 100% to 34-70%. Sites 5 and 6 represent two soils across the MNT and MAT boundary.…”
Section: Soil Ph and Base Saturationmentioning
confidence: 99%
“…Based on a study in a localized area at the northem foothills, Valentine and Binkley ( 1992) concluded that the topography is primarily responsible for soil pH variations among all controlling factors. Walker et al (1998) realized the pH boundary between the MNT and MAT and its implications in ecology and wildlife habitat. Ping et al (1998) found that key to the nature of this boundary is that soil pH and base saturation changes along a climate transect from the Arctic Coast to the Brooks Range.…”
mentioning
confidence: 99%
“…It has been argued (Freeman et al, 2001;Evans et al, 2002;Tranvik et al, 2002) that a change in climate and hydrology in high latitude regions could liberate large amounts of previously inactive C during a prolonging thawing period as total organic C (TOC) or dissolved organic C (DOC), and new studies in Swedish lakes have shown that a great deal of this organic C is mineralized as CO 2 (Sobek et al, 2005) or CH 4 during its transport to the sea. Whereas TOC export can be described as a function of water discharge, i.e., flushing of organic rich top soils (podzols are dominating) during spring flood (Boyer et al, 1996;Smedberg et al, 2006), gaseous fluxes are also positive related to soil moisture and evapotranspiration (Walker et al, 1998) that will increase with global warming. However, even during frozen periods, streamflow is dominated by "old" groundwater.…”
Section: Past and Possible Future Changes In Si Fluxesmentioning
confidence: 99%
“…The waterlogging that accompanies peat accumulation influences vegetation distribution throughout the region (Walker and Walker, 1996;Walker et al, 1998), and Sphagnum mosses play a key role in paludification on the North Slope by acidifying soils, lowering soil-nutrient levels, and retaining water. In poorly drained areas, active layers are typically only 25 cm thick as a result of insulation by organic surface layers (Everett and Brown, 1982;.…”
Section: Study Areamentioning
confidence: 99%
“…In the Arctic Foothills, most of the vegetation is moist acidic tundra (Sphagno-Eriophoretum) dominated by dwarf shrubs (Betula nana, Ledum palustre, Salix planifolia pulchra), tussock sedges (Eriophorum vaginatum) and acidophilous mosses, among which Sphagnum species are prominent. An important point for the interpretation of pollen records is that ericaceous shrubs, Sphagnum moss, and Rubus chamaemorus (cloudberry) are characteristic of moist acidic tundra vegetation today (D. Walker et al, 1989Walker et al, , 1998Walker et al, , 2001M. Walker et al, 1994;Shaver et al, 1996;Walker and Walker, 1996).…”
Section: Study Areamentioning
confidence: 99%